2009
DOI: 10.1007/s11695-009-9897-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Gastrojejunal Anastomotic Stricture with Multifilament and Monofilament Sutures after Hand-Sewn Laparoscopic Gastric Bypass: A Prospective Cohort Study

Abstract: Anastomotic GJ stricture is a common and well-known complication of laparoscopic gastric bypass for morbid obesity. Hand sewing with monofilament suture significantly lowered the frequency of this complication, and hence, monofilament should be the suture material of choice for this suturing technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 12 publications
1
18
0
1
Order By: Relevance
“…The rate of stricture formation quoted in the literature ranges from 0 to 33.3% [6][7][8][9][10]. Furthermore, these rates have encompassed circular stapled, linear stapled, and handsewn GJ anastomotic techniques, and all of these techniques have reported both high and low rates of stricture formation [11], which makes the literature confusing. Carrodeguas and colleagues reviewed 1,291 patients at their institution and published a stricture rate of 7.3% [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The rate of stricture formation quoted in the literature ranges from 0 to 33.3% [6][7][8][9][10]. Furthermore, these rates have encompassed circular stapled, linear stapled, and handsewn GJ anastomotic techniques, and all of these techniques have reported both high and low rates of stricture formation [11], which makes the literature confusing. Carrodeguas and colleagues reviewed 1,291 patients at their institution and published a stricture rate of 7.3% [15].…”
Section: Discussionmentioning
confidence: 99%
“…Higa et al [22] reported a stricture rate of 4.9% with handsewn anastomosis in a series of 1,040 cases; this corresponds with our stricture rate. Adana et al [11] reported a randomized study comparing stricture rates using monofilament and braided suture in a handsewn GJ, and the stricture rates were 0.7 and 9.7%. This stricture rate needs to be reproduced by other groups to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vasquez et al (11) report fewer complications at the gastro-jejunal anastomosis in their series of 315 gastric bypasses when the reinforcing suture applied on the 25-mm circular stapling is made out of resorbable thread. Ruiz de Adana et al (12), in their prospective cohort study on 242 LGB procedures with manual anastomosis, obtained 9.5% of stenosis in the gastro-jejunal anastomoses with resorbable multifilament suture, and 0.7% in the group receiving resorbable monofilament thread.…”
mentioning
confidence: 96%